Adaptation of Basic Chemistry Learning with Green Chemistry Oriented - Mitarlis, Mitarlis; Azizah, Utiya; Yonata, Bertha (Universitas Negeri Malang, 2022)
The principles of green chemistry can be implemented in chemistry learning. Basic Chemistry learning with Green Chemistry insight can also be adapted to high school chemistry learning. This study aims to describe basic chemistry learning, adaptations of chemistry learning and design of chemistry learning with green chemistry insight at high school based on the results of previous research. The method used in this study was a systematic review, namely a systematic narrative review conducted by mapping or systematic mapping study. Sources of data from electronic documents were traced through Google searching, ERIC document data, and research gates with the keywords green chemistry and green education. The results show that basic chemistry learning can apply several principles of green chemistry. The principles (preventing/reducing waste, saving energy, and using renewable feedstock) can be implemented in several chemistry topics. The topics cover separating mixtures, chemical reactions, fundamental laws of chemistry, acids and bases, and reaction rates. Also, green chemistry can be adapted to high school chemistry even though it has not been stated in the chemistry curriculum. The design of chemistry learning with green chemistry insight can apply several learning models, such as Problem Based Learning (PBL), Project Based Learning (PjBL), and Inquiry or Contextual Teaching and Learning (CTL).